The happy discovery of the "facilitated collection" - Gallo-León, José-Pablo (Anuario ThinkEPI, 2017)
Lorcan Dempsey has formulated the brilliant concept of the "facilitated collection", which represents what the academic library collection should be today. Library collections have traditionally been dominated by print logic, where size and closeness are core values. This logic has been altered by the possibilities of the Internet and digital collections. Presently, collections can be built around the user's needs and as a result libraries must assure access to documents that are not necessary owned by the library. Therefore, collection development should be based on cooperation between institutions, which entails a great deal of effort because of the constant updating, maintenance of catalogs, and discarding the vision that assimilates a collection to a property.
Keywords: Facilitated collection; Collection management; Collection development; Academic libraries.